Pengembangan Sistem Manajemen Penjadwalan Les Privat Berbasis Web (Studi Kasus: Naoyuki Academic Center) - Misbakhul Kharis; Fajar Pradana; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Naoyuki Academic Center is a Japanese language learning institution. Every week, Naoyuki conducts a learning agenda in accordance with the curriculum that has been prepared according to current needs. Until now, the preparation of the schedule in Naoyuki is done by using Excel and takes up to 3 days in arranging the schedule of tutors and students. Through the scheduling problem at Naoyuki, the learning scheduling management system will then be developed. This system was developed using the Object Based Approach from the Analysis to the Implementation stage. The system is implemented using the PHP programming language and the MVC concept while using the Boostrap and Laravel framework. The test results of the system using White-Box and Black-Box show that all functionalities are in accordance with the requirements specified. The test results show 100% for all White-Box test cases. And shows 100% valid for Black-Box testing of 24 functional systems. For compatibility testing all system functionality can run in some browsers but there are still problems with the appearance and performance of the system.